(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Opioid addiction poses a significant public health challenge. Evaluating the effectiveness of methadone substitution therapy (MST) in both social and clinical domains is crucial for developing targeted interventions. Objective: This study aimed to assess the effectiveness of MST for opioid addiction at the Methadone Treatment Facility in Thu Dau Mot City in 2024. Methods: A cross-sectional descriptive study was conducted, employing structured questionnaires and medical record reviews of 133 patients who had received MST for at least nine months at the facility. Results: Social Impact: After nine months of treatment, the proportion of patients with stable employment significantly increased from 29.3% to 70.6% (p<0.001), while the unemployment rate decreased from 24.1% to 3.0% (p<0.001). No instances of legal infractions were reported during the treatment period (p<0.001), and 97% of patients reported improved social relationships with family and friends. Treatment Outcomes: While treatment adherence was 100%, only 55.6% of patients achieved optimal treatment outcomes. Patients responding positively to treatment were 1.6 times more likely to achieve these outcomes compared to non-responders (p=0.015). Conclusion and Recommendations: MST demonstrates a positive impact on social reintegration and treatment adherence. However, the relatively low rate of optimal treatment outcomes, primarily attributed to opioid relapse, necessitates enhanced interventions. Strengthening patient counseling and education on relapse prevention, fostering healthy lifestyle skills, promoting social engagement, and addressing high-risk relationships are crucial. These interventions should be particularly emphasized for patients showing suboptimal treatment response.